J05 Task-specific Training In Huntington's Disease: A Randomised, Controlled Feasibility Trial. (17th September 2014) - Quinn, L; Debono, K; Dawes, H; Rosser, A; Nemeth, AH; Quarrell, O; Rickards, H; Tabrizi, SJ; Trender-Gerhard, I; Kelson, M; Townson, J; Busse, M
Abstract : Background: Motor learning principles suggest that interventions to promote mobility should incorporate goal-directed activities within the specific environmental context to achieve better outcomes. Aims: We aimed to determine the feasibility, safety and potential benefit of goal-directed, task-specific mobility training for individuals with mid-stage HD. Methods: Thirty individuals were enrolled and randomised into control or intervention groups in this multi-centre trial. Training focused on walking, sit-to-stand and standing activities, twice a week for 8 weeks at home. Goal attainment scaling was used to individualise and direct the intervention. Time to complete 5 chair sit-to-stand repetitions (5CST) was recorded at each intervention session. Adherence and adverse events were monitored. Adjusted between-group comparisons on standardised outcome measures (blinded) at 8 and 16 weeks informed assessment of benefit. Results: Loss to follow up was minimal (2 participants); adherence in the intervention group was excellent (96.9%). Ninety-two percent (92%) of goals were achieved at the end of the intervention and 46% achieved much better than expected outcome; the majority of goals focused on improving walking endurance and confidence. Mean (95% CI) improvement in 5CST in intervention group was 5.5 sec (2.2, 8.9). There was no clear evidence of benefit on standardised outcome measures at 8- or 16-week assessments. Conclusions: Most participants exceeded goal expectation with excellence adherence. While the programme was well received by people with HD and facilitated achievement of personal mobility goals, training intensity and specificity was likely insufficient to achieve systematic improvements in standardised outcome measures.